Improving workflows in a hospital through the application of lean thinking principles and simulation - Cardoso, Nuno (2017)
This paper focuses on the external consultation and internment services in a hospital from Northern Portugal. The main goal was to improve the patient and hospital technical assistant's flows at these services applying principles of Lean HealthCare, i.e., principles of Lean Thinking adapted to the health care services. Several problems were identified in these services. Examples are deficient information and signage, long queues, lengthy waiting times resulting from various service inefficiencies. In order to solve these problems, some proposals for improvement were made, using Lean tools such as kanban systems or Visual Management and other tools like simulation using Arena software. These proposals may lead to a better management of working time for technical assistants, shorter queues and waiting times, reduced travel for patients and technical assistants by avoiding overlapping of workflows.